Sustainability Education in the 21st Century: Incorporating Environmental Awareness in K-12 Curriculum - Jean Monika (Yayasan Azhar Amanaa Yogyakarta, 2024)
This study investigates the integration of sustainability education into K-12 curricula, focusing on the incorporation of environmental awareness in contemporary educational settings. As global environmental issues become increasingly pressing, the role of education in fostering a generation that understands and values sustainability is critical. This research examines current practices in sustainability education across various schools, highlighting the diverse methods used to incorporate topics such as climate change, recycling, and resource conservation into the curriculum. The study reveals significant variation in how schools implement sustainability education, influenced by factors such as geographic location, available resources, and institutional support. Teachers' experiences with teaching sustainability are explored, including their strategies, challenges, and the impact of sustainability education on student engagement and learning outcomes. Additionally, the study evaluates the professional development available to educators and the support systems in place to aid in the effective implementation of sustainability topics.The findings indicate that while some schools have successfully integrated sustainability education into their programs, there remain considerable challenges, including resource limitations and varying levels of teacher preparedness. The study provides recommendations for policymakers and educators on enhancing the integration of sustainability education, emphasizes the importance of community and institutional support, and identifies areas for future research. This research contributes to the understanding of how sustainability education can be effectively implemented in K-12 settings, with implications for improving environmental literacy and shaping educational practices and policies.